Associations Among Mothers' Depression, Emotional and Learning‐Material Support to Their Child, and Children's Cognitive Functioning: A 16‐Year Longitudinal Study. Issue 6 (17th April 2018) - Wu, Victoria; East, Patricia; Delker, Erin; Blanco, Estela; Caballero, Gabriela; Delva, Jorge; Lozoff, Betsy; Gahagan, Sheila
Abstract : This study examined the associations among maternal depression, mothers' emotional and material investment in their child, and children's cognitive functioning. Middle‐class Chilean mothers and children ( N  = 875; 52% males) were studied when children were 1, 5, 10, and 16 years (1991–2007). Results indicated that highly depressed mothers provided less emotional and material support to their child across all ages, which related to children's lower IQ. Children with lower mental abilities at age 1 received less learning‐material support at age 5, which led to mothers' higher depression at child age 10. Mothers' low support was more strongly linked to maternal depression as children got older. Findings elucidate the dynamic and enduring effects of depression on mothers' parenting and children's development.